The Impact of Political Involvement on Firms’ Financial Performance - Shira, Ruba Khalid (International Journal of Economics and Financial Issues, 2024)
Political involvement helps businesses to obtain key government resources and support. Political involvement assists businesses to take actions that reduce uncertainty, provide shield and environmental dependence from the environmental threats that can directly impact their performance. This study aims to investigate the impact of political involvement on banks’ sustainable performance in selected South Asian economies (Pakistan, Bangladesh, India, and Sri Lanka). The data is collected from DataStream for the period of 2013-2022. The Generalized Method of Moments (GMM) is employed to analyze the results. The study finds that political involvement negatively affects the firm’s sustainable performance. This study is helpful for management of the organizations and shareholders to increase firm performance by reducing political involvement.